International Financial Integration, Sovereignty, and Constraints on Macroeconomic Policies - Kletzer, Kenneth (IMF Working Papers; Working Paper, 2006)
This paper considers the consequences of international financial market integration for national fiscal and monetary policies that derive from the absence of an international sovereign authority to define and enforce contractual obligations across borders. The sovereign immunity of national governments serves as a fundamental constraint on international finance and is used to derive intertemporal budget constraints for sovereign nations and their governments. It is shown that the appropriate debt limit for a country allows for state-contingent repayment. With noncontingent debt instruments, debt renegotiation occurs in equilibrium with positive probability. A model of tax smoothing is adopted to show how information imperfections lead to conventional bond contracts that are renegotiated when a critical level of indebtedness is reached. Renegotiation is interpreted in terms of nominal and real denominated bonds, and implications are drawn about the intertemporal borrowing constraint for monetary policies, the accumulation of reserve assets, and current account sustainability.